DEPARTENT HEALTH HUMAN SERVICES (Tufts Archival Research Center, 2007)
Memo to all OASH employees from the department of health and human services regarding a smoke free work environment. States that OASH will be at the forefront of this proposal and that smoking in public places without proper ventilation will be banned.